Implementasi Internet of Things (IoT) pada Sistem Pemantauan Kelembapan Udara di Perpustakaan UBSI - Rian Septian Anwar; Nani Agustina; Novita Indriyani (Journal of Students‘ Research in Computer Science, 2025)
Libraries, particularly academic libraries like those at UBSI, store valuable collections of books, manuscripts, and digital archives. The preservation of these physical assets is constantly threatened by environmental factors, primarily fluctuating temperature and humidity. Uncontrolled high humidity accelerates the growth of mold and mildew, leading to irreversible damage to paper-based materials. Manual monitoring systems are often inefficient, costly, and susceptible to human error. This research aimed to develop and implement a real-time, Internet of Things (IoT)-based air humidity monitoring system to ensure optimal environmental conditions for collection preservation in the UBSI Library. The system utilizes the NodeMCU ESP8266 microcontroller and the SHT30 sensor, chosen for its high accuracy and stability, to continuously collect humidity data. This data is transmitted via Wi-Fi to a Firebase real-time database and visualized on a dynamic web dashboard. The prototype was tested for accuracy and reliability, showing minimal deviation (less than 3%) compared to commercial hygrometers. The results confirm that the IoT system successfully provides remote, continuous, and highly accurate monitoring, enabling prompt intervention by library staff when humidity levels exceed the safe threshold (50%–60%). This innovative approach significantly enhances collection preservation efficiency and reduces potential conservation costs. The system built not only successfully collects data, but also processes it into easily understood information, thus fulfilling the initial objective of overcoming the inefficiency of manual monitoring.